Persistent Opioid Use Following Cesarean Delivery: Patterns and Predictors Among Opioid-naive Women. Issue 3 (September 2017) - Bateman, B.T.; Franklin, J.M.; Bykov, K.; Avorn, J.; Shrank, W.H.; Brennan, T.A.; Landon, J.E.; Rathmell, J.P.; Huybrechts, K.F.; Fischer, M.A.; Choudhry, N.K.
Abstract : ( Am J Obstet Gynecol. 2016;215(3):353.e1–353.e18) According to the US Centers for Disease Control and Prevention and other leading health care organizations, between 1999 and 2010 the rate of opioid medication overdose resulting in death among women increased 5-fold. With over a third of all deliveries in the United States being cesarean deliveries and opioids being prescribed as postsurgical analgesics to these patients, the risk of overdose increases. Hence, the purpose of this study was to identify the risks and behavior patterns of women with initial opioid exposure (opioid-naive women) in the setting of routine medical care (eg, postcesarean pain medicine prescriptions) associated with them becoming persistent opioid users.